The design of beyond LEO mission scenario for a biological payload with a cubesat. - Pratnekar, Marko (Cranfield University, 2019)
CubeSat technology has been well established in the area of space engineering for almost two decades. Because of standardisation of components and procedures, development and launch costs of space missions are greatly reduced and space based experiments become more affordable for the broader community. Up to now, all CubeSat missions except for one have been launched in Low Earth Orbit. With recent developments and new launch opportunities, sending CubeSat missions with various on board experiments beyond Low Earth Orbit into interplanetary space becomes possible. Major space agencies have ambitious plans to send human space missions to Mars and other bodies in the Solar System. Traveling beyond Earth’s orbit, living cells in the human body will be exposed to harmful effects of space radiation. Therefore, before such interplanetary mission takes place, detailed study of effects of space radiation on human like mammalian cells should be conducted. An interplanetary mission based on the CubeSat platform would be the most affordable way of conducting such experiment. The main aim of the reported research work is to investigate if adequate space radiation protection and strict thermal environment requirement can be achieved and maintained for biological payload with higher forms of living cells, within a CubeSat spacecraft platform during interplanetary flight. This thesis is divided into a theoretical part – the literature review and methodological part – numerical simulations which are for space radiation performed by NASA developed software OLTARIS and for thermal analysis of the spacecraft and installed components with ESATAN –TMS modelling software. From the performed research work it can be concluded that adequate radiation protection can be implemented within the CubeSat payload compartment, so as not to exceed the acute dose limit set even during long duration interplanetary space flight, while at the same time leaving enough payload volume for the installation of the experimental biological payload and experimental instrumentation within the extra installed radiation protection. In maintaining the thermal environment inside the payload bay with biological material as well as in maintaining the survival temperature of some electronic components, careful heat management and active thermal control – additional electrical heating is required. There was no requirement for active cooling in the realistic mission scenarios considered.
Keywords: space radiation; thermal environment; interplanetary space flight; mammalian cells; OLTARIS; ESATAN-TMS; spacecraft